The Literary Thing : History, Poetry, and the Making of a Modern Cultural Sphere - Rosinka Chaudhuri (New Delhi Oxford University Press, 2014)
Exploring certain cultural turning points in the history of Bengali literature, this study investigates the place of the aesthetic, the political, and the collective in the composition of a literary culture. By doing so, it reveals the relevance and significance of this sphere to our self-making as Indians.
Include Index.
History, Poetry, and the Making of a Modern Cultural Sphere.
Keywords: Bengali literature -- Nationalism in literature -- Bengali poetry -- Culture in literature